The Monopsony Paradox: A Counterview on Reclaiming Single-Buyer Leverage in Monopolistic Silicon Supply Chains - Kaul, Shiwain (ExcelingTech, 2026)
Monopsony theory predicts that a single buyer facing multiple sellers should command decisive pricing power. This paper challenges that assumption in the context of specialized silicon procurement, where a sole buyer often confronts a monopolistic or near-monopolistic supplier. Drawing on practitioner experience in strategic sourcing and supply chain leadership within the consumer electronics industry, this paper identifies and formalizes the Monopsony Paradox: the counterintuitive phenomenon whereby single-buyer leverage diminishes – rather than intensifies – as supplier specialization and mutual dependency increase. This research makes three distinct contributions to supply chain management theory and practice. First, it defines and validates the Monopsony Paradox as a distinct theoretical phenomenon, providing a structured explanation of inverted buyer leverage in specialized silicon markets. Second, it develops the Triple-Constraint Negotiation Framework (TCNF), a novel procurement approach that simultaneously optimizes cost extraction, supply security, and supplier viability – representing a fundamental departure from conventional zero-sum negotiation models. Third, it provides empirical validation through detailed case analysis demonstrating how TCNF enabled a substantial reduction in manufacturing value-add while qualifying alternative suppliers and preserving vendor financial stability, with implications applicable across monopolistic procurement categories. The framework is illustrated through sensor silicon procurement in the consumer electronics industry, where significant double-digit cost reductions were achieved in the vendor’s manufacturing value-add while simultaneously qualifying an alternative supply network and preserving the incumbent vendor's financial health. Unlike conventional procurement models that treat vendor negotiations as zero-sum, this framework argues that short-term profit maximization through aggressive cost extraction can be counterproductive when the buyer depends on a sole-source vendor for mission-critical components. The paper offers practical implications for procurement leaders operating in bilateral dependency environments across semiconductor, display, battery, and other specialized technology supply chains.